Community and Local Government Synergy in Building Regional Cultural Validation - Harianto II Harianto II; Zulfitri Zulfitri; Teguh Satria Amin (Jurnal Educatio FKIP UNMA, 2023)
Cultural diversity in Indonesia is one of the charms that this equatorial country has. And of course this cultural diversity must be preserved so that it does not become extinct and is also lost in foreign cultures that enter Indonesia in this era of globalization. In managing this culture, of course the local government, the community, and the customary institutions formed in the midst of the community must work together and synergize to carry out cooperation to preserve culture. And the research conducted this time is to describe and also analyze the implementation of synergy, supporters and also obstacles to community and local government cooperation to build regional cultural validation. This study used descriptive qualitative method. The synergy of the local government and the community in carrying out cultural preservation can be seen from several factors such as programs, implementers, to facilities and infrastructure. This form of cooperation and synergy is expected to provide positive results for regional cultural validation as well as social change in society. Other supporting factors are regulations that are easy to apply in the community environment and also the application of principles and also regulatory provisions. The inhibiting factors themselves are human resource capacity and also the problem of conversion areas and also regional autonomy.